Mini Review: Phytochemistry and Pharmacological Activity of Hibiscus Rosa-Sinensis Plant - Amani Amer Tawfeeq; Tahany Amir Tawfeeq; Ibrahim S Abaas; Sumayah Hassan Salah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Hibiscus rosa-sinensis, rose mallow, is one of the Malvaceae family. Hibiscus rosa sinensis is valued as an attractive, ornamental addition to a healing plant. traditionally to treat skin conditions, menorrhagia, bronchitis, demulcent, abortion, antifertility, contraception, and diuretics Numerous phytochemical components, including flavonoids, mucilage, alkaloids, saponins, phenolic acid, and polyphenols, define it. It has been documented that hibiscus flowers can be used as an anti-inflammatory, antipyretic, analgesic, and asthmatic. Numerous investigations have demonstrated that Hibiscus rosa-sinensis flowers have anti-oxidant, antifungal, and antibacterial qualities. This work aimed to mini-review and establish the available evidence and information about Hibiscus rosa-sinensis and its bioactive constituents and pharmacological activity uses. This study suggests future work for more novel chemical structural characterization quality control, molecular docking studies, and clinical trials.